Is Marxism a sort of Scientific Research Programme? A proposal for the adaptation of Lakatos's methodology to the history of Marxism - Macías Fernández, Carlos Maximiliano [UNESP] (My University, 2020)
Those who continued the political tradition founded by Marx and Engels inherited just a basic body of doctrine. The disciples had to develop different theories of middle range to address the tactical and strategic issues faced by the movement. Meanwhile, the arising anomalies in the domain of political struggle had to be solved whenever they seemed to refute the original predictions from the founding fathers. This article suggests that it might be useful to consider the development of Marxism with the methodology proposed by the philosopher of science Imre Lakatos for the rational reconstruction of science. As in any Research Program, for the classics of Marxism their project counted with a positive heuristic and a negative heuristic. Some examples of classical debates are intended to show how Lakatos's methodology has the virtue of explaining recurring labels within this tradition - such as dogmatism, orthodoxy, heterodoxy or revisionism - as coherent positions when examined in relation to both the “core” of the Marxist program and its practical applications. In conclusion, the conditions for a critical and controlled adaptation of Lakatos's methodology to the peculiarities of Marxism are specified. The relevance of this adaptation is convincing thanks to its ability to make controversies within Marxism understandable as combinations of theoretical arguments and practical results.
¿El marxismo se comporta como un Programa de Investigación Científica? Propuesta de adaptación de la metodología de Lakatos
Keywords: Historiography of Marxism; Imre Lakatos; Marxist Controversies; Marxist Epistemology; Methodology of Scientific Research Programmes